Engravings from the Strasbourg Edition of Virgil’s Aeneid (1502): On the Issue of the Migration of Wooden Blocks and Images in 16th-Century Europe - Subbotina, Olga V. (Actual Problems of Theory and History of Art, 2023)
Migration processes were an important part in the artistic life of early Modern Europe. Not only craftsmen and artistic artels moved from city to city, from region to region, but also books, albums of samples, local traditions, and techniques traveled with them. Based on a cycle of engravings (137 woodcuts) for Virgil’s “Works”, published by the major Strasbourg publisher Johann Grüninger in 1502, the article focuses on two aspects of the problem connected with prevailing artistic and craft practices in Europe at the end of the 15th–16th centuries. Firstly, it is the problem of the circulation of the typographical material, the ways of its use within one publishing house, its possible movements and reusing by other owners Secondly, it is the fate of the printed images  created by the artists on I. Grüninger’s order. This book was significant and notable for the Strasbourg publisher. It differed from the previous ones because whole blocks were used for woodcuts instead of small wooden block combinations; it was also different in terms of complexity and richness of the figurative language of the visual narrative. A new tradition of illustrating Virgil appeared in the workshop of Johann Grüninger, which later spread widely not only in the German lands, but also in France and Italy. It dominated for half a century and remained influential for European masters until the beginning of the 17th century. The author has compared different editions and analyzed not only the principles of reusing the same engraving boards, but also the different approaches to copying engravings in Italian and French printing houses of the time.
Keywords: Johann Grüninger; wood blocks migration; Virgil’s Aeneid; incunabula; paleotype; woodcut; visual narrative; text and image; copying